Some field observations of the endemic Sulawesi rails - Lambert, Frank (KUKILA, 1989)
The remarkable endemic avifauna of Sulawesi includes two little known rails, Snoring Rail Aramidopsis plateni, and Bald-faced Rail Gymnocrex rosenbergii. Snoring Rail is known from 11 specimens from North, Central and South-east Sulawesi (White & Bruce 1986), all but one having been collected before 1940. The latest specimen was obtained from villagers in Lore Lindu National Park, Central Sulawesi, in 1980 (Watling 1983, P.B. Taylor pers. comm.). There have been no documented sightings of Snoring Rail since the 1930's (Ripley 1977). Bald-faced Rail is known from just one Sulawesi specimen, and three from Peleng (White & Bruce 1986), although other specimens have apparently been collected in the past (1940) but were eaten or lost (Coomans de Ruiter 1947). Very little is known about the habits of either species. During a three week visit to Lore Lindu National Park, Central Sulawesi, in 1987, I observed one, and probably two, Snoring Rails in Ahe Sopu River valley at c.750m on 7 July. The following day, I again heard, but did not see, Snoring Rail, but saw a Bald-faced Rail in the vicinity.